Bimetallic lanthanide complexes that display a ratiometric response to oxygen concentrations - Sørensen, T; Kenwright, A; Faulkner, S (Royal Society of Chemistry, 2015)
A pair of hetero-bimetallic lanthanide complexes containing terbium and europium ions have been prepared by coupling kinetically stable complexes together using an Ugi methodology to incorporate a naphthyl chromophore. Both complexes exhibit emission from terbium and europium in solution. The terbium centred emission varies with dissolved oxygen concentration, while the europium intensity remains essentially constant in one of the complexes.